2020
DOI: 10.1177/1075547020960465
|View full text |Cite
|
Sign up to set email alerts
|

Stars—They’re Sick Like Us! The Effects of a Celebrity Exemplar on COVID-19-Related Risk Cognitions, Emotions, and Preventative Behavioral Intentions

Abstract: Research on exemplification suggests that celebrity health exemplars can exert a greater influence on public risk perceptions than exemplars featuring noncelebrities. In the aftermath of actor Tom Hanks’s announcement that he tested positive for COVID-19, an online experiment compared the effects of his exemplar to an identical noncelebrity exemplar. Hanks’s disclosure increased perceptions of susceptibility to the virus. The celebrity exemplar also increased anxiety, which increased intentions to engage in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
10
1
1
Order By: Relevance
“…PSP, therefore, seemed to be relevant for taking protective actions. Cohen (2020) similarly found positive relationships between PSP with celebrities and prevention behavior intentions. Depending on the experimental condition, people read either that Tom Hanks or a businessman had contracted the coronavirus.…”
Section: The Mediating Role Of Pspmentioning
confidence: 78%
“…PSP, therefore, seemed to be relevant for taking protective actions. Cohen (2020) similarly found positive relationships between PSP with celebrities and prevention behavior intentions. Depending on the experimental condition, people read either that Tom Hanks or a businessman had contracted the coronavirus.…”
Section: The Mediating Role Of Pspmentioning
confidence: 78%
“…Recently, Cohen (2020) provided evidence for the applicability of the availability heuristic in a health context. In particular, she found that exposure to celebrities suffering of COVID‐19 increased anxiety towards the disease.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…This assumption is supported by recent findings showing that fear of the virus and perceptions of its dangerousness lead to a higher compliance with NPIs (Abdelrahman, 2020; Harper et al, 2020). Furthermore, it is in line with the risk‐as‐feelings approach by Loewenstein et al (2001), which suggests that “emotion—specifically affective responses to threats such anxiety, worry, and fear—is viewed as a dimension of risk perception that is capable of exerting its own discrete and direct influence on behavior.” (Cohen, 2020, p. 728).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Specifically, social media plays a role in shaping public perceptions of risk and outrage during crises (Ophir, 2018; Quinn, 2018; Rossman et al, 2018). Cohen (2020) examined the influence of celebrities who shared their COVID-19 experiences on social media on public risk perceptions and found the presence of celebrities influenced public perception of disease susceptibility and increased public engagement in prevention behavior. Though social media provides opportunities for experts to quickly share information to the public, barriers exist in using social media for effective risk communication as members of the general public also share inaccurate information (Malecki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%